(3TQM GdTGajIs - (3QVi GdOjf eMeO Hf GdMSf GdGSJQGHGPis; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg abO YReJ Ydi Cf CTQM ebOeI GHf GdMGLH s
(3BNQgG (B:s
(3JOd Ydi GdjGA dCf GdcSQI dGJeGd dgG Cda KGdKI Yf hGh Je GdcJGH s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1021s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUQas